2021
DOI: 10.1590/2447-536x.v27i3.2337
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal endogenous changes in response to the exogenous 6-benzylaminopurine application in pre- and post-harvesting lilium flower stalks

Abstract: Phyto-hormones play a key role in regulating plant responses to stress. Cytokines are a type of phyto-hormones involved in the regulation of many important biological processes related to growth, development, and response to environmental variables. The exogenous application of cytokines increases the possibility of delaying senescence; however, this is a physiological process, and, under certain conditions, degradation processes may be triggered. The effect of 6-bencilaminopurine application and the endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For instance, Herrera-Isidron et al [47] recently proposed differential cytokinin perception depending on certain developmental events during the organogenesis in potatoes. In addition, it is still not clear whether cytokinin signaling takes place from one or more than one site at the cellular level (endoplasmic reticulum and/or plasma membrane), if the action is equal in all tissues or if it depends on the tissue, its developmental stage, and/or the action of signalling molecules from different origins [48], or if synergies exist between endogenous levels of hormones and exogenously applied PGRs [49]. Therefore, how exogenously applied BAP and 2iP (among other cytokinins) might act at the cellular or tissue level, and how this interaction is specifically translated into morphogenesis in vitro for different genotypes or plant species, cannot be stated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Herrera-Isidron et al [47] recently proposed differential cytokinin perception depending on certain developmental events during the organogenesis in potatoes. In addition, it is still not clear whether cytokinin signaling takes place from one or more than one site at the cellular level (endoplasmic reticulum and/or plasma membrane), if the action is equal in all tissues or if it depends on the tissue, its developmental stage, and/or the action of signalling molecules from different origins [48], or if synergies exist between endogenous levels of hormones and exogenously applied PGRs [49]. Therefore, how exogenously applied BAP and 2iP (among other cytokinins) might act at the cellular or tissue level, and how this interaction is specifically translated into morphogenesis in vitro for different genotypes or plant species, cannot be stated.…”
Section: Discussionmentioning
confidence: 99%
“…The restricted irrigation (RI) was performed with 8 emitters per linear bench meter, it started from the stem emergence and was applied at the same frequency than NI throughout the crop cycle. Fertilization started from stem emergence, approximately 20 days after planting, with a complete nutrient solution applied with irrigation water for both NI and RI (Mantilla et al, 2021). Only stalks with 5 flower buds were considered for the postharvest test.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, previous studies have reported on the role of phytohormones in mitigating water stress in lilium plants, finding the exogenous application of 6-BAP as a tool to obtain stronger plants, with a longer vase life. That is why, in recent years, research has been carried out with the aim of increasing the biosynthesis of endogenous cytokinin (Luo, et al, 2021), improving the understanding of the mechanism that regulates senescence (Kanojia and Dijkwel, 2018) and intervene to delay this process during the post-harvest of cut flowers and other horticultural products (Gill et al, 2023, Mantilla et al, 2021.…”
Section: Introductionmentioning
confidence: 99%